Demand for long acting contraceptive methods among married HIV positive women attending care at public health facilities at Bahir Dar City, Northwest Ethiopia - Gelagay, Abebaw Addis (Reprod Health, 2015)
BACKGROUND: The use of long acting contraceptive methods (LACMs) is one of the strategies for preventing mother-to-child transmission (MTCT) of HIV. Studies noted that significant proportion of unintended pregnancy among HIV positive women was due to contraceptive failure mainly of short term contraceptives. This highlights the need to use most effective types of modern contraception, long acting contraceptive. However, studies conducted on demand for long acting contraceptive methods in this particular group of people are scarce in Ethiopia. This study aimed to assess demand for long acting contraceptive methods and associated factors among married reproductive age women attending care at Antiretroviral treatment (ART) clinics in public health institutions at Bahir Dar City, Northwest Ethiopia. METHODS: Institution-based cross-sectional study was conducted among 654 systematically selected women attending care in ART clinics in public health facilities at Bahir Dar city from March to April, 2014. A structured and pretested interviewer administered questionnaire was used to collect data. Data were entered using EPI info version 3.5.3 and then exported to SPSS version 16 for analysis. Descriptive statistics were used to describe the socio-demographic and economic characteristics of the study participants. Logistic regression analyses were employed to identify factors associated with demand for long acting contraceptive methods. Odds ratios with 95 % CI were used to assess the presence and strength of association. RESULTS: A total of 654 respondents have participated in the study (response rate 99. 09 %). The demand for long acting contraceptive methods was 36.7 % (95 % CI: 33.2 %, 40.6 %). The odds of demand for LACMs among HIV positive women who were living in urban were three times [AOR = 3.05, 95 % CI: 1.34, 6.89] higher than those who were living in rural. The odds of demand for LACMs among the respondents who were in elementary educational level were two times [AOR = 2.31, 95 % CI: 1.34, 3.99] more likely as compared to those who had no formal education. HIV positive women who had four or more alive children were almost four times [AOR = 3.86, 95 % CI: 1.62, 9.20] more likely to have demand for LACMs than those who had one child or had no child at all. Those who had desire to give birth after 2 years were nearly six times more likely [AOR = 5.68, 95 % CI: 3.05, 11.58] to have demand for LACMs and women who had no birth intension were eight times more likely [AOR = 7.78, 95 % CI: 4.15, 14.58] to have demand for LACMs as compared to those who had intention to have birth within 2 years. Women who had past experience on LACMs had six times more likely [AOR = 6.35, 95 % CI: 4.09, 9.87] to have demand for LACMs than those who hadn’t any experience. The odds of demand for long acting contraceptive methods among HIV positive women who had heard myths about LACMs was 55 % less [AOR = 0.45, 95 % CI: 0.29, 0.68] than those women who hadn’t heard myths. CONCLUSIONS: Demand for long acting contraceptive methods in this study was low. There was high unmet need for LACMs. Myths about LACMs were common in the community and were the major barriers for the promotion and utilization of the methods. Demand creation on LACMs and bringing attitudinal change related to myths through provision of information, education and communication are recommended. Moreover, giving greater attention for rural residents is important.